Ravenna : its role in earlier medieval change and exchange - Herrin, Judith; Nelson, Janet L. (Janet Laughland), 1942- (Institute of Historical Research, 2016)
In the long-debated transition from late antiquity to the early middle ages, the city of Ravenna presents a story rich and strange. From the fourth century onwards it suffered decline in economic terms. Yet its geographical position, its status as an imperial capital, and above all its role as a connecting-point between East and West, ensured that it remained an intermittent attraction for early medieval kings and emperors throughout the period from the late fifth to the eleventh century.